(untitled) (Journal of the College of Basic Education, 2025)
The aim of this research is to develop instructional units based on the Hanven Bik model and to determine their effect on learning the triple jump event. The researchers adopted the experimental method to achieve the research objective. The research population was intentionally selected from second-year students at the College of Physical Education and Sports Sciences, University of Ashur, totaling 61 male and female students. They were distributed into two classrooms: Classroom (A), which included 28 male students, and Classroom (B), which included 33 students (27 males and 6 females). The research sample was limited to male students, consisting of 18 students from section (B) who were randomly selected to represent the experimental group taught using the Hanven Bik model. Another 18 students from section (A) formed the control group, which was taught using the traditional method. Prior to the start of the experiment, the researcher ensured equivalence between the two groups through a pre-test for learning the triple jump event, with the assistance of a support team after providing the participants with information and guidance about the test and how to perform it. The researchers designed eight instructional units based on the Hanven Bik model, which were used to teach the experimental group over a period of 10 weeks. Meanwhile, the control group was taught using the traditional method. A learning test for the triple jump event was also prepared. The researchers used the Statistical Package for the Social Sciences (Spss) to analyze the data. The results indicated the positive impact of the Hanven Bik model on learning the triple jump event among second-year students at the College of Physical Education and Sports Sciences, University of Ashur.